THE SOCIO-ECONOMIC PRECONDITIONS OF TRANSFORMATION OF UKRAINIAN ECONOMY - Р. Б. Попівняк; О. І. Шавалюк (Ринкова економіка: сучасна теорія і практика управління)
The features of transformation of Ukrainian economy are examined on the modern stage of its development. Problems which arise up in the process of transformation are investigated. Directions of optimization of socio-economic development are grounded on the basis of transformation dynamics rationalization. The article is focused on the function of the state in transformation all sociallu-economic modifications with an accent on an individual Ukrainian road and searching of ways of improving its economy. Thus, the basic current trends of social and economic transformations of Ukrainian economy are further deepening of social inequality of the majority of people by economic, political and social parameters which provokes the tension in our society. On the one hand, the social inequality is caused by the formulated recently system of incomes distribution and injustice in economic, political and social resources availability. On the other hand, such inequality is the result of Ukrainian state policy.